Perancangan Sistem Informasi Penyewaan Lapangan Futsal Berbasis Web - Sonia Dara Fortunata Sonia; Christian Cahyaningtyas (Infact: International Journal of Computers, 2023)
Angkasa Futsal is one of the futsal field rental places in the city of Bengkayang. In the futsal field rental service method, it still uses the old method, namely the manual method which will have an impact on prospective customers and owners of places of tranquility. This study aims to build a web-based futsal field rental information system at Angkasa Futsal to make it easier for customers to make rentals and owners to manage rental data. The stages of research include problem assistance, literature review, data collection methods, needs analysis, system design, implementation and testing. Making the information system is carried out using the Waterfall method and designing the Uified Modeling Language (UML) model. This system can be used by 2 users, customer and admin.